Trophectoderm morphology predicts outcomes of pregnancy in vitrified-warmed single-blastocyst transfer cycle in a Chinese population - Chen, Xiaojiao (J Assist Reprod Genet, 2014)
PURPOSE: In this study, we estimated the effect of blastocoele expansion, ICM and TE quality after warming and culture on the rates of clinical pregnancy, live birth and miscarriage in vitrified-warmed single-blastocyst transfer cycle in a Chinese population. METHODS: A retrospective analysis of 263 cycles of vitrified-warmed single-blastocyst transfers was performed. RESULTS: The blastocysts with higher TE grade significantly increased the rates of clinical pregnancy (OR = 0.59, 95 % CI, 0.35–0.99, P = 0.045, grade (A + B) vs grade C) and live birth (OR = 0.55, 95 % CI, 0.32–0.94, P = 0.029, grade (A + B) vs grade C). And the association between TE grade and the rate of live birth didn’t change after the number of repeated cycles was adjusted (OR = 0.55, 95 % CI, 0.32–0.95, P = 0.033, grade (A + B) vs grade C). The number of repeated cycles was a confounding factor significantly different between the live birth and no live birth groups. By contrast, neither blastocoele expansion nor inner cell mass was statistically related to the rates of clinical pregnancy, live birth and miscarriage. CONCLUSIONS: Our data firstly provided the evidence that TE grading, but not ICM grading, was significantly associated with the clinical pregnancy rate and live birth rate in vitrified-warmed blastocyst transfer cycles in a Chinese population. TE morphology may help predict outcomes of pregnancy in single-blastocyst transfer.